IMPLEMENTASI MEDIA DIORAMA UNTUK MENUMBUHKAN KREATIVITAS SISWA DALAM PEMBELAJARAN IPS - Devi Sri Wahyuni; Jauhari, Najib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of diorama media in fostering students' creativity in social studies (IPS) learning in class VIID of SMPN 19 Malang. The background of this research is the low creativity and enthusiasm of students when social studies material is delivered only through lecturing and textbooks, so that concrete and visual learning media are needed to stimulate students' imagination and creative expression. This research used a qualitative approach with a descriptive method. Data were collected through documentation and interviews with students of class VIID SMPN 19 Malang, then analyzed through data reduction, data display, and conclusion drawing. The results show that the implementation of diorama media was carried out through three stages, namely planning, making the diorama, and presenting the work, and was proven to increase students' creativity, which can be seen from the variety of ideas, the composition of objects, the use of materials, and students' confidence in presenting their work. This study concludes that diorama media is an effective alternative learning media to foster students' creativity in social studies learning at the junior high school level.